Ten years experience with a novel modification of plastibell circumcision - Ashraf Hammed; Ahmed Abd Elgffar Helal; Refaat Badway; Samir Hammed Goda; Abdelaziz Yehya; Mohamed Abd Razik; Ahmed Elshamy; Omar Elsamahy (Wolters Kluwer Medknow Publications, 2014)
Background: Plastibell device is a satisfactory method of circumcision in infants. However the most common post-operative complication was bleeding (especially from the frenulum site). As a result, we introduce a novel modification of the device to prevent this complication. Patients and Methods: A prospective comparative study of Plastibell circumcision in infants up to the age of 12 months was conducted, using conventional Plastibell device and modified Plastibell device circumcision. In The first group (1000 infants), circumcision was performed with conventional Plastibell device while in the second group (4500 infants), circumcision was done with modified Plastibell device. Results: The mean age was 8 weeks. The mean operating time were 8.5 min and 5.9 min for conventional Plastibell ring and modified Plastibell device circumcision respectively. The most common postoperative complication in first groups was bleeding. Conclusion: This modified Plastibell device, prevents the most series complication of bleeding. It is fast and ensures excellent cosmoses compared with the standard Plastibell template circumcision. Also it is easy to perform and allows the paediatric surgeon to achieve consistently excellent cosmetic results. Moreover, the shorter operating time makes circumcision by the modified Plastibell device a more practical method. The technique will be described in detail.